Mice in social conflict show rule-observance behavior enhancing long-term benefit. Issue 1 (December 2017) - Choe, Il-Hwan; Byun, Junweon; Kim, Ko; Park, Sol; Kim, Isaac; Jeong, Jaeseung; Shin, Hee-Sup
Abstract Disorderly resolution of conflict is costly, whereas orderly resolution by consent rules enables quick settlement. However, it is unclear whether non-human animals can make and observe rules to resolve conflict without aggression. Here we report a new behavioral paradigm for mice: a modified two-armed maze that uses wireless electrical brain stimulation as reward. First, the mice were individually operant-trained to initiate and then receive the reward at the signaled arm. Next, two mice were coupled and had to cooperate to initiate reward but then to compete over reward allocation. Mice develop and observe a rule of reward zone allocation that increases the total amount of reward and reward equity between the pair. In the mutual rule-observance behavior, positive reciprocity and tolerance to the other's violation are also observed. These findings suggest that rodents can learn to make and observe rules to resolve conflict, enhancing long-term benefit and payoff equity. Resolving conflict in an orderly way is beneficial, but it is unclear whether non-human animals make and observe such rules. Here, authors show that mice spontaneously develop and observe such rules, thereby increasing their total, individual reward as well as the reward equity with other mice.